Histopathological and histomorphometric analysis of the small intestine in wistar rats subjected to daily alcohol intake (Research, Society and Development, 2024)
The excessive consumption of alcohol poses a significant public health concern due to its detrimental effects on individual well-being, particularly on the gastrointestinal (GI) tract. Chronic ethanol ingestion leads to morphological and functional alterations in the GI tract, affecting epithelial cells and resident microbial flora, thus impairing intestinal absorption. This study aimed to assess the impact of chronic ethanol consumption on small intestinal histological morphology. Animals were divided into control (water), 5% ethanol, and 20% ethanol groups, with 10 animals in each. Over 80 days, ethanol consumption was monitored ad libitum. Histopathological and histomorphometric analyses of the small intestine were conducted. Results revealed similar daily liquid consumption among the groups. However, alcoholic groups exhibited increased mononuclear cells, eosinophils, and villus degeneration compared to the control group. Ethanol-treated animals also displayed reduced villi extension, indicating structural damage to the intestine. Chronic ethanol consumption induced a chronic inflammatory pattern and deterioration of intestinal structures. In conclusion, regardless of alcohol content, chronic ethanol consumption adversely affects the gastrointestinal tract. This study underscores the importance of understanding the pathological effects of alcohol on the GI system and emphasizes the need for interventions to mitigate its impact on public health.